Chemical senses: a context-based approach to chemistry teaching for lower secondary school students - Edelsztein, Valeria Carolina (2020)
The Context-Based Science Education (CBSE) approach promotes the inclusion of scientific concepts in everyday situations. In this work, we present a non-traditional context-based teaching experience on the subject of chemical senses that seeks, through a unique didactic instrument, to generate cognitive conflicts in order to promote conceptual change from "common sense"to science-based ideas. This experience encourages the active role of the students and involves simple experiences with everyday materials. It was carried out with 95 students from 12 to 15 years old. The contents developed during the experience were focused on taste and smell and the concepts of perception and sensation. The activities were designed to promote students' self-awareness on their previous knowledge in order to achieve a sustainable learning by constructing appropriate scientific concepts. Assessment of students' motivation for learning and their conceptual change - from common sense ideas to science based ideas - was done through an initial survey and a post-test. Students' perception on their commitment and enjoyment about the approach has been evaluated through a metacognitive poll. The results show that the activities were highly motivating and that students were aware of their improvement in knowledge and their own commitment to the task throughout the entire experience.